Effects of an innovative educational program on female athletes' knowledge and habits related to pelvic floor care: a quasi-experimental study - Vico-Moreno, Elena; Bosch-Donate, Elisa; Fernández-Domínguez, Juan Carlos; Sastre-Munar, Andreu; Bachero-Mena, Beatriz; Romero-Franco, Natalia (Frontiers in Public Health, 2025)
The physical demands of sports require female athletes to be aware of pelvic floor (PF) care. However, knowledge about PF dysfunctions and unhealthy habits remains insufficient in sports populations. Innovative and specific educational strategies are needed to engage female athletes. This study evaluated the effects of an online educational program on PF knowledge and care habits in female athletes. A three-session online program with practical content and 3D models was implemented. Of the 130 registered athletes (35.9 ± 11.2 years old), 70 fully attended (FA), 23 partially attended (PA), and 37 did not attend (NA). Before and 4 weeks after the program, participants completed a questionnaire assessing: (1) demographics and sports data; (2) PF symptomatology; (3) knowledge of urinary incontinence (UI), female sexual dysfunction (FSD), ano-rectal incontinence (ARI), and pelvic organ prolapse (POP); and (4) habits during micturition, defecation, and sports practice. FA and PA athletes rated the utility of the program (0–10 scale). After the program, FA athletes showed improved knowledge of UI (p = 0.032), FSD, ARI, and POP (ps < 0.001) compared to baseline and NA athletes (ps < 0.001). FA athletes also reduced unhealthy habits during micturition (p = 0.003) and defecation (p = 0.003), and had fewer unhealthy habits overall compared to NA athletes. The utility of the program was rated 8.4 points. A three-session innovative online educational program proved effective in enhancing PF-related knowledge and improving care habits among female athletes.